Pengaruh Penggunaan Media Boneka Tangan (Hand Puppet) terhadap Peningkatan Bahasa Reseptif Anak Usia 5-6 Tahun di PAUD SOS HKBP Sitabotabo - Halima Marisa Nababan; Winarti Agustina; Hisardo Sitorus (IAKN Tarutung, 2022)
The purpose of this study was to determine the effect of using Hand Puppet media on the improvement of receptive language for children aged 5-6 years at PAUD SOS HKBP Sitabotabo. The method used in this research is quantitative inferential statistics. The population is all children aged 5-6 years in PAUD SOS HKBP Sitabotabo, totaling 30 people. Data were collected using a positive closed questionnaire of 30 items. The results of data analysis showed that there was an effect of using Hand Puppet Media on the Improvement of Receptive Language for Children aged 5-6 Years in PAUD SOS HKBP Sitabotabo.: 1) Test requirements analysis: a) positive relationship test obtained values rxy = rtabel(a=0,05,n=30) = 0,361 Thus, it is known that there is a positive relationship between the X variable and the Y variable. b) The test of a significant relationship is obtained by the value of thitung= 3,980 ttabel(a=0,05,dk=n-2=28 )= 2,048 thus there is a significant relationship between variable X and variable Y. 2) Test the effect: a) Test the regression equation, the regression equation is obtained b) Test the coefficient of regression determination (r2) = 36%. 3) Test the hypothesis by using the F test obtained Fhitung ≥ Ftabel that is 15,84 1,62 Thus Ha is accepted and H0 is rejected.